The Link between Economic Growth, Crime and Deterrence Measures in Nigeria - Adekoya, Adenuga Fabian; Razak, Nor Azam Abdul (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The level of crime in Nigeria has become devastating and in order to put more sanity into the economy and the country at large, the Government has embarked on different deterrence measures in curbing crime. Thus, this study examined the interaction of deterrence measures with crime in order to see how economic growth was affected when they were used in curbing crime at different instances. That is, the interaction of deterrence measures with crime informed us how they have helped in lowering crime in Nigeria for a better economic growth to subsist. The deterrence measures considered in this work are in line with the rational choice theory being the cost of crime imposed on the society. Furthermore, this study considered data from 1975 to 2013 with the use of autoregressive distributed lag model. Moreover, the results showed that crime dependency on deterrence measures asymmetrically constituted means of lowering economic growth in the country. Hence, this study suggested that prosecution should be well funded and in order to curb crime and improve economic growth in Nigeria. That is, this would afford the country to reduce the congestion of prison inmates and thus, it would discourage long waiting trials.